More Than Just Attractive: How CCL2 Influences Myeloid Cell Behavior Beyond Chemotaxis - Gschwandtner, Martha; Derler, Rupert; Midwood, Kim S. (Frontiers in Immunology, 2019)
Monocyte Chemoattractant Protein-1 (MCP-1/CCL2) is renowned for its ability to drive the chemotaxis of myeloid and lymphoid cells. It orchestrates the migration of these cell types both during physiological immune defense and in pathologic circumstances, such as autoimmune diseases including rheumatoid arthritis and multiple sclerosis, inflammatory diseases including atherosclerosis, as well as infectious diseases, obesity, diabetes and various types of cancer. However, the scope of CCL2’s functions extends well beyond its original characterization as a chemoattractant. Emerging evidence shows that it impacts leukocyte behavior, influencing adhesion, polarization, effector molecule secretion, autophagy, killing and survival. The direction of these CCL2-induced responses is context dependent and in some cases synergistic with other inflammatory stimuli. The involvement of CCL2 signaling in multiple diseases renders it an interesting therapeutic target, although current targeting strategies have not met early expectations in the clinic. A better understanding of how CCL2 affects immune cells will be pivotal to the improvement of existing therapeutic approaches, and the development of new drugs. Here, we provide an overview of the pleiotropic effects of CCL2 signaling on cells of the myeloid lineage, beyond chemotaxis, and highlight how these actions help to shape immune cell behavior and tumor immunity.